Climate‐driven vital rates do not always mean climate‐driven population. (9th June 2016) - Tavecchia, Giacomo; Tenan, Simone; Pradel, Roger; Igual, José‐Manuel; Genovart, Meritxell; Oro, Daniel
Abstract: Current climatic changes have increased the need to forecast population responses to climate variability. A common approach to address this question is through models that project current population state using the functional relationship between demographic rates and climatic variables. We argue that this approach can lead to erroneous conclusions when interpopulation dispersal is not considered. We found that immigration can release the population from climate‐driven trajectories even when local vital rates are climate dependent. We illustrated this using individual‐based data on a trans‐equatorial migratory seabird, the Scopoli's shearwater Calonectris diomedea, in which the variation of vital rates has been associated with large‐scale climatic indices. We compared the population annual growth rate λ i, estimated using local climate‐driven parameters with ρ i, a population growth rate directly estimated from individual information and that accounts for immigration. While λ i varied as a function of climatic variables, reflecting the climate‐dependent parameters, ρ i did not, indicating that dispersal decouples the relationship between population growth and climate variables from that between climatic variables and vital rates. Our results suggest caution when assessing demographic effects of climatic variability especially in open populations for very mobile organisms such as fish, marine mammals, bats, or birds. When a population model cannot be validated or it is not detailed enough, ignoring immigration might lead to misleading climate‐driven projections.